Analysis of Distribution and Marketing Efficiency of Pineapples from a Sharia Economic Perspective - Iskandar, Dadang Ishak; Eviatun, Esti; Rumianti, Susti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The agricultural sector plays an important role in long-term economic development and rural economic recovery in Indonesia. The development of agricultural-based businesses and sustainable agricultural systems is needed to improve the quality of human resources and agricultural products. Horticultural commodities, such as fruit, have high economic potential and can be a source of income for farmers. However, there are several obstacles in the agricultural sector, such as competition with other horticultural products, low quality and quantity of local supplies, and a lack of transparent market information. In addition, distribution in Islam has principles that can be applied in the context of the distribution of wealth and economic resources in Islam, such as justice, equality, public benefits, prohibition of exploitation, and social solidarity. This research aims to analyze pineapple marketing distribution and pineapple marketing efficiency from a sharia economic perspective. The research method used is field research using primary and secondary data. The research results show that there are two marketing distribution channels that are used, namely marketing distribution channel I and marketing distribution channel II. Marketing distribution channel I involves farmers selling directly to the city without intermediaries, while marketing distribution channel II involves collectors buying from farmers and selling to the city. Keywords: Distribution, Efficiency, Marketing